2001
DOI: 10.1542/peds.107.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole for Prophylaxis Against Candidal Rectal Colonization in the Very Low Birth Weight Infant

Abstract: Prophylactic administration of fluconazole to the VLBW infant for the first 28 days of life is safe and results in a decreased risk of rectal colonization by candidal species. Larger studies to determine the effect of prophylaxis on candidal septicemia and development of resistance in such a selective high-risk group are warranted before initiation of routine prophylaxis.fluconazole, very low birth weight infant, prophylaxis, candidal sepsis, sensitivities to fluconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
2
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 25 publications
6
177
2
5
Order By: Relevance
“…Most of the data comes from the growing body of literature assessing fluconazole prophylaxis in this population. Five randomized controlled trials addressing this question also looked at the effect of fluconazole on liver function tests [52,[65][66][67][68]. These five studies included 726 infants in the NICU and two found statistically though not clinically significant increases in aspartate aminotransferase (AST) and alanine aminotransferase (ALT).…”
Section: Toxicities Side Effects and Drug Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the data comes from the growing body of literature assessing fluconazole prophylaxis in this population. Five randomized controlled trials addressing this question also looked at the effect of fluconazole on liver function tests [52,[65][66][67][68]. These five studies included 726 infants in the NICU and two found statistically though not clinically significant increases in aspartate aminotransferase (AST) and alanine aminotransferase (ALT).…”
Section: Toxicities Side Effects and Drug Interactionsmentioning
confidence: 99%
“…To date there have been five randomized controlled trials (RCTs) [52,[65][66][67][68], eight retrospective reviews [19,20,[73][74][75][76][77][78], and a Cochrane review [79] examining fluconazole prophylaxis in neonates.…”
Section: Neonatal Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonization at multiple sites and CVC colonization have been reported as independent risk factors for candidal BSI [100]. The use of fluconazole prophylaxis seems to be effective against fungal colonization as well as to prevent candidal BSI [91][92][93][94][95][101][102][103]. None of the prophylaxis studies has reported changes in the fluconazole susceptibility of the Candida strains.…”
Section: Bloodstream Infectionsmentioning
confidence: 99%
“…Prophylaxis studies conducted in NICUs [91,94,[101][102][103] have shown no signs of fluconazole resistance or reduced susceptibility regarding C. parapsilosis isolates. Some have hypothesized that this phenomenon is due to the low total fluconazole doses received [91].…”
Section: Emergence Of Fluconazole Resistance In C Parapsilosis (Iii)mentioning
confidence: 99%